MO457: Diffusion-MRI Predicts Decline of Renal Function in Chronic Kidney Diseases and Kidney Allograft Patients. (3rd May 2022) - Berchtold, Lena; Crowe, Lindsey; Combescure, Christophe; Kassai, Miklos; Aslam, Ibtisam; Legouis, David; Moll, Solange; Martin, Pierre-Yves; de Seigneux, Sophie; Vallée, Jean-Paul
Abstract: BACKGROUND AND AIMS: Kidney cortical interstitial fibrosis is highly predictive of renal prognosis and is currently assessed by the evaluation of a biopsy. Diffusion-weighted magnetic resonance imaging is a promising non-invasive tool to evaluate kidney fibrosis. We recently adapted a diffusion-weighted imaging sequence, allowing for the discrimination between the kidney cortex and medulla. The cortico-medullary difference in apparent diffusion coefficient (ΔADC) correlated to histological interstitial fibrosis. The aim of this study was to assess whether ΔADC as measured with diffusion-weighted magnetic resonance imaging is predictive of renal function decline and dialysis in chronic kidney diseases (CKD) and kidney allograft patients. METHOD: We performed a prospective study including 197 patients. We measured ΔADC in 43 CKD patients [estimated glomerular filtration rate (eGFR) 55 mL/min/1.73m 2 ] and 154 kidney allograft patients (eGFR 53 ml/min/1.73m 2 ). Patients underwent a renal biopsy and diffusion-weighted magnetic resonance imaging, within 1 week of biopsy. Follow-up was 2.2 years in median. During follow-up, laboratory parameters were measured. Primary outcome was defined as rapid decline of renal function (eGFR decline > 30% or dialysis initiation) during follow-up. RESULTS: Patients with low ΔADC (<0 x10 -6 mm 2 /s) had 5.4 times more risk of rapid decline of renal function or dialysis [95% confidence interval (CI): 2.29–12.58; P < 0.001]. After correction for renal function at baseline and proteinuria, low ADC still predict renal function loss with a hazard ratio (HR) of 4.62 (P < 0.001, 95% CI 1.56–13.67). CONCLUSION: We demonstrate in this study that low ΔADC is a predictor of renal function decline and dialysis initiation in CKD and kidney allograft patients, independent of baseline renal function and proteinuria.